Geochemical evolution of groundwater under the influence of human activities： A case study in the southwest of Poyang Lake Basin. (May 2022) - Mao, Hairu; Wang, Guangcai; Liao, Fu; Shi, Zheming; Huang, Xujuan; Li, Bo; Yan, Xin
Abstract: Groundwater quality continues to be threatened globally by anthropogenic activities including excessive use of chemical fertilizers and sewage discharge. However, few studies on the evolution of groundwater chemistry have systematically characterized human and natural effects, while which is of great importance for sustainable water resources management. In this study, hydrochemical data and multiple tracers (δ 15 N–NO3 -, δ 18 O–NO3 -, and 87 Sr/ 86 Sr) were employed to elucidate the geochemical evolution of groundwater in an intensive human activity area - the southwest of Poyang Lake Basin where is characterized by the highly complex hydrogeological environment with the diversity of aquifer types and lithology. Combining fuzzy c-means (FCM) clustering with natural background levels (NBLs) analyses, groundwater was divided into four groups with hydrological and statistical significance: groundwater in recharge zones (group 2-1 and group 3), transition zones (group 2-2) and discharge zones (group 1). Using the ions relations and 87 Sr/ 86 Sr, we found that the dissolved components of groundwater in recharge zones were controlled by natural processes (water-rock interactions and groundwater runoff conditions), and human activities have altered the natural geochemical evolution of groundwater in transition zones and discharge zones. Multi-tracer approach (δ 15 N–NO3 -, δ 18 O–NO3 -, and 87 Sr/ 86 Sr) were used to analyze the sources of nitrate in groundwater. The results showed that the high nitrate load in groundwater was predominately from sewage, and the groundwater quality in local areas was also influenced by NH4 + fertilizer and manure. In addition, nitrate in groundwater was controlled by land use types that groundwater flows through, depending on hydrogeological conditions and soil properties. Inverse geochemical models were developed and constrained to evaluate the relative contributions of natural and anthropogenic sources and to establish a conceptual model of groundwater geochemical evolution in the study area. This study provides a way to evaluate the relative contributions of natural and anthropogenic sources on groundwater quality and explore the geochemical evolution of groundwater in human activity areas. Highlights: Groundwater was hydrochemically divided into 4 groups along generalized flow directions. Groundwater hydrochemistry in recharge zones were controlled by water-rock interactions. High level of NO3 − and NH4 + in groundwater appeared in transition and discharge zones. N-components were predominately from sewage and locally from fertilizer and manure. A conceptual model of groundwater geochemical evolution was proposed.